The Roses that Grew from the Cracks in the Canadian Culture Mosaic - Plummer, Patricia (Revue YOUR Review (York Online Undergraduate Research), 2022)
This research examines the perception of Canada through two generations of immigrants. Canada has been viewed as a cultural mosaic, an inclusive safe haven, by immigrants, regardless of gender, age, or religion—always welcoming, a beautiful and flawless “masterpiece.” However, does Canada truly fulfill this depiction? Are we a cultural mosaic? Are the tools for success provided to immigrants and to our citizens? Uncovering the marginalized stories of individuals who immigrated to Canada for a better life, filled with opportunity, will reveal the real narrative of our nation.